Cordyceps mushroom with increased cordycepin content by the cultivation on edible insects - Turk, Ayman; Abdelhamid, Mohamed A. A.; Yeon, Sang Won; Ryu, Se Hwan; Lee, Solip; Ko, Sung Min; Kim, Beom Seok; Pack, Seung Pil; Hwang, Bang Yeon; Lee, Mi Kyeong (Frontiers in Microbiology, 2022)
Cordycepin is the major constituent of Cordyceps mushroom (or Cordyceps militaris) with therapeutic potential. Insects are the direct sources of nutrients for Cordyceps in nature. Therefore, optimized condition of Cordyceps cultivation for efficient cordycepin production was explored using six edible insects as substrates. The highest yield of cordycepin was produced by the cultivation on Allomyrina dichotoma and was 34 times that on Bombyx mori pupae. Among insect components, fat content was found to be important for cordycepin production. Especially, a positive correlation was deduced between oleic acid content and cordycepin production. The transcriptional levels of cns1 and cns2, genes involved in cordycepin biosynthesis, were higher in Cordyceps grown on A. dichotoma than on other insects tested. The addition of oleic acid to the substrates increased cordycepin production together with the transcriptional levels of cns1 and cns2. Therefore, Cordyceps with high content of cordycepin can be secured by the cultivation on insects.